UNGKAPAN ETNIS PETANI JAWA DI DESA JAPANAN, KECAMATAN CAWAS, KABUPATEN KLATEN: KAJIAN ETNOLINGUISTIK - Dwi, Haryanti; Wahyudi, Agus Budi (Universitas Muhammadiyah Surakarta, 2007)
The study aims at describing ethnic expressions and their intention of Javanesefarmers at Japanan district based on their social and cultural context. It uses descriptivequalitative research and the data are analyzed by Spreadlyâs ethnographicanalysis. The analysis tries to describe the linguistic units and their intension basedon the social and cultural contexts. The findings show that the ethnic expressionsconsist of words and phrases. Those expression are used in all steps of agriculturalactivities done by the farmers, for examples, pranatamangsa âmonthsâ, mangsa udanâwet seasonâ, macul âto hoeâ, mangsa sada âthe eleventh monthâ, gawe pinihan âcultivationof seedlingsâ, mangsa kanem âthe sixth monthâ, ketiga âdry seasonâ, luku andgaru âplowsâ, ngrabuk âto fertilizeâ, matun âto clear away the weeds in the farmsâ,mangsa panen âharvest moonâ, dewi sri âriceâ, den bagus âratsâ, methik/guwakan âmisticor ritual ceremony before harvesting timeâ, sedhekah bumi/bersih desa/rasulan âmisticceremony after harvesting with wayang kulit show entitled sri boyong, sri mulih, or srisadana.